Marginalized Malay females: a socio-demographic analysis on female prisoners in the Malaysian prisons / Rachel Samuel and Roaimah Omar - Samuel, Rachel; Omar, Roaimah (Division of Research and Industry Linkages , UiTM Melaka, 2014)
The number of females incarcerated in Malaysian prisons grew from 2909 in 1998 to 3511 in the year 2000 (15,07 rate per 100,000 inhabitants) (Malaysian Crime Index, 2002). More than 79% (n=95) of those interviewed in five Malaysian prisons were Malays. These women were mainly between the ages of 20 and 39, divorced and were incarcerated for various offences. The imprisonment seems harder on women who were mothers as they are totally dependent on their support network to care for their children. In majority of the cases, there is no contact with the younger children and strained relationships with the older children. In many cases, both the female and her husband/boyfriend were both in prison as crime was carried out together with one party abetting with the other. About half the women grew up in broken homes. These women who have ended up in prison after having grown up in broken homes, currently have children whose mothers and at times, their fathers too, are absent from their lives. Hence the cycle of violence-continues.